The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.33448/rsd-v11i12.34179
|View full text |Cite
|
Sign up to set email alerts
|

Fauna edáfica e serrapilheira associadas á dois fragmentos florestais na Amazônia Meridional

Abstract: O equilíbrio ambiental pode ser avaliado observando as características do ambiente, e da população de grupos de organismos específicos, considerados bioindicadores. Assim, o objetivo desse trabalho é avaliar a fauna edáfica e a serrapilheira em dois fragmentos florestais na Amazônia Meridional, analisando sua utilização como potenciais bioindicadores. Foram realizadas análises em um fragmento florestal (A1) e uma área de recuperação (A2), usando armadilhas pitfall para fauna edáfica e acúmulo e decomposição de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…The variations in the deposition of the litter can be justified by different species and crop ages (Castro et al, 2022). Sales et al (2020) evaluating litter formation in the southern Amazon region, observed a value of 12.58 Mg ha -1 year -1 in a forest area.…”
Section: Litter Contributionmentioning
confidence: 99%
“…The variations in the deposition of the litter can be justified by different species and crop ages (Castro et al, 2022). Sales et al (2020) evaluating litter formation in the southern Amazon region, observed a value of 12.58 Mg ha -1 year -1 in a forest area.…”
Section: Litter Contributionmentioning
confidence: 99%